Design and Synthesis of Fluorescence-Labeled TAK779 Analogs as Chemical Probes - Hiroyuki Konno; Takuya Saito; Taichi Aota; Daiki Takanuma; Mizuho Okuyama; Chikako Yokoyama (Molecules, 2025)
N,N-Dimethyl N-[4-[[[2-(4-methylphenyl)-6,7-dihydro-5H-benzocyclohepten-8-yl]carbonyl]amino]benzyl]tetra-hydro-2H-pyran-4-aminium chloride (TAK779) has a potent binding affinity for the chemokine receptor CCR5 and low cytotoxicity; however, their interaction remains unknown. We designed and synthesized four fluorescence-labeled TAK779 analogs as chemical probes. Although the binding properties of the fluorescence-labeled TAK779 analogs for CCR5 could not be determined, it was found that they penetrate the cell membranes and localize to the microtubes of HeLa cells.